Spatial assessment and number of bicycle stations in an educational setting (case study: Iran University of Science and Technology - Karmegam, Karuppiah; Torabi, Hamide; Dehghani, Zahra; Naeini, Hasan Sadeghi (University of Tehran- Kish International Campus KIC, 2022)
Universities are scientific and educational spaces with a focus on young influentials. In this regard, the importance of attention and design for this group of society is obvious to everyone. Moreover, due to today’s neutral and sedentary lifestyle which causes many harms and problems for individuals and society, the need of creating mobility and motivating people to do sports activities is of great importance. For this purpose, according to the capability of the available space on the campus and the above-mentioned issues, it was decided to study the grounds for establishing a bicycle station at the university. This study aimed to provide a suitable location for bicycle stations in the university and determine the appropriate number of bicycles for students to use. Data was collected through articles, questionnaires, field observations, and LMS (e-learning management system). The questionnaire was conducted in two stages. In the first stage, 217 students participated to assess the need for a bicycle station, and the second phase of the survey was conducted by 4 experts (Industrial Design Professors) to classify the criteria related to determining the location of stations. During the studies and questionnaires, 13 spots were determined for the stations in which 6 bicycles can be positioned in each station